PEMBUATAN PUPUK ORGANO-MINERAL FERTILIZER (OMF) PADAT DARI LIMBAH INDUSTRI BIOETANOL (VINASSE) (Jurnal Bahan Alam Terbarukan, 2015)
Organo-mineral fertilizer solid was generated from liquid-waste vinasse with the addition of other materials as variations such as filter cake, boiler ash, urea, and NPK through the evaporation of water content in the material. Each solid OMF has a different mixture. OMF A made of evaporated vinasse or sticky vinasse, OMF B made of vinasse and urea, OMF C made from vinasse and filter cake, omf D made of vinasse and boiler ash 2 : 2, OMF E made of vinasse and boiler ash 2 : 4, OMF F made of vinasse, filter cake, and boiler ash, OMF A3 made of vinasse and 3% NPK, OMF made of A6 vinasse and 6% NPK, OMF A9 made of vinasse and 9% NPK. OMF analysis includes NPK and C/N ratio. Solid OMF which meet the SNI (Indonesian National Standard) are OMF A3, OMF A6, OMF A9 based on the quantity of NPK and C/N ratio where NPK is a source of primer macro nutrients on the plant while the C/N ratio equilibrium will determine the equilibrium of the vegetative and generative stage. NPK content and C/N ratio of OMF A3 are 0,63%, 0,45% ,0,38%, and 10,30, respectively.OMF A6 was 0,59%, 0,52% ,0,41%, and 13,66, respectively as well as OMF A9 are 0,68%, 0,52% ,0,45% and 14,16, respectively. OMF that meet SNI applied to the watermelon plants. OMF that gives the best results in plants is OMF A9 compossed from vinasse and NPK 9% because the plants growth faster shown based on plant height and stem diameter, leaf shape, flower and fruit appearance time.